SHP2 inhibition triggers anti-tumor immunity and synergizes with PD-1 blockade - Mingxia Zhao; Wenjie Guo; Yuanyuan Wu; Chenxi Yang; Liang Zhong; Guoliang Deng; Yuyu Zhu; Wen Liu; Yanhong Gu; Yin Lu; Lingdong Kong; Xiangbao Meng; et al. (Elsevier, 2019)
Tyrosine phosphatase SHP2 is a promising drug target in cancer immunotherapy due to its bidirectional role in both tumor growth promotion and T-cell inactivation. Its allosteric inhibitor SHP099 is known to inhibit cancer cell growth both in vitro and in vivo. However, whether SHP099-mediated SHP2 inhibition retards tumor growth in vivo via anti-tumor immunity remains elusive. To address this, a CT-26 colon cancer xenograft model was established in mice since this cell line is insensitive to SHP099. Consequently, SHP099 minimally affected CT-26 tumor growth in immuno-deficient nude mice, but significantly decreased the tumor burden in CT-26 tumor-bearing mice with intact immune system. SHP099 augmented anti-tumor immunity, as shown by the elevated proportion of CD8+IFN-γ+ T cells and the upregulation of cytotoxic T-cell related genes including Granzyme B andPerforin, which decreased the tumor load. In addition, tumor growth in mice with SHP2-deficient T-cells was markedly slowed down because of enhanced anti-tumor responses. Finally, the combination of SHP099 and anti-PD-1 antibody showed a higher therapeutic efficacy than either monotherapy in controlling tumor growth in two colon cancer xenograft models, indicating that these agents complement each other. Our study suggests that SHP2 inhibitor SHP099 is a promising candidate drug for cancer immunotherapy. KEY WORDS: Cancer immunotherapy, SHP2, SHP099, PD-1, Colon cancer